Mind the intention-behavior gap: a qualitative study of post-myocardial infarction patients’ beliefs and experiences with long-term supervised and self-monitored physical exercise - Alexander Svenningsen; Sylvia Söderström; Silvana Bucher Sandbakk; Lars Gullestad; Kaare Harald Bønaa; Ulrik Wisløff; Siri Marte Hollekim-Strand (BMC Sports Science, Medicine and Rehabilitation, 2024)
Abstract Background Many post-myocardial infarction (MI) patients struggle with physical activity behavior change (BC) for life-long secondary prevention. There is limited knowledge about factors influencing long-term physical activity BC among post-MI patients. This qualitative study aimed to explore the beliefs and experiences related to post-MI patients’ physical activity BC process following a year’s participation in a supervised and self-monitored exercise program: the Norwegian Trial of Physical Exercise After MI (NorEx). Methods We conducted a qualitative study, performing in-depth semi-structured interviews with a randomly selected sample of NorEx participants when they were scheduled for cardiopulmonary exercise testing after one year of participation. Interviews were transcribed verbatim and the data was analyzed by applying reflexive thematic analysis. Results Seventeen participants (n = 4 female [24%]; median age, 61 years; median time since index MI, 4 years) were recruited and interviewed once. Analysis resulted in four main themes (nine sub-themes): (1) Personal responsibility to exercise (Exercise is safe, Health benefits, Habitual exercise); (2) Peer social support for a sense of safety and belonging (Social exercise, Supervision is preferred); (3) Research participation transformed exercise beliefs (High-intensity exercise is superior, Personal Activity Intelligence (PAI) promotes exercise adherence); and (4) Mind the intention-behavior gap (Initial anxiety, Lack of continued follow-up). Conclusions Several participants reported that they were able to maintain exercise BC during a year’s participation in NorEx. Nevertheless, a perceived lack of continued and individualized follow-up made some participants struggle with motivation and self-regulation, leading to an intention-behavior gap. Therefore, our findings suggest there is a need for individualized and continued social support and supervision from health and exercise professionals to maintain long-term exercise BC for secondary prevention among post-MI patients. Trial registration The NorEx study has been registered at ClinicalTrials.gov (NCT04617639, registration date 2020-10-21).